Peningkatan Pengetahuan tentang Kanker Serviks pada Kader sebagai Upaya Peningkatan Cakupan Deteksi Dini Kanker Serviks - Kartika Adyani; Emi Sutrisminah; Hanifatur Rosyidah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Cervical cancer is still a scourge for women in the world. The low coverage of early detection of cervical cancer is one of the causes of high mortality due to late treatment. One factor influencing women's participation of childbearing age in cervical cancer early detection is access to information and cadres' role. This community service aims to increase the knowledge of health cadres about early detection of cervical cancer as a requirement for health promotion to women. The methods used in this activity were lectures, question and answer, and discussion. The participants were 13 health cadres in Sumberrahayu Village, Limbangan District. The result is an increase in good category knowledge (15.5 to 76.9%). Increasing cadres' knowledge can be used as a model for community empowerment in upgrading the childbearing age women's knowledge about early detection of cervical cancer.